The influence of agricultural insurance on agricultural carbon emissions: evidence from China’s crop and livestock sectors - Jin, Yue; Wang, Xinya; Wang, Qian (Frontiers in Environmental Science, 2024)
Agricultural insurance is an important tool for promoting low-carbon agriculture and achieving the “Carbon Peaking and Neutrality” goal. Using panel data from 31 provinces in China from 2001 to 2020, this study analyzes the carbon-reducing effects of agricultural insurance in both crop and livestock sectors. The results show that: (1) Agricultural insurance can decrease agricultural carbon emissions. (2) For crops, agricultural insurance reduces carbon emissions through green technical efficiency, and for livestock products by green technological advances. (3) Agricultural insurance could lower carbon emissions from the livestock and crop sectors in the eastern region. The carbon-reducing benefits of agricultural insurance for the crop sector are seen in the agricultural, agro-pastoral, and pastoral domains; for the livestock sector, these impacts are only seen in the agricultural domains.